KERALA MODEL RESPONSIBLE TOURISM –AN EVALUATION - Nissar P. and Munavver Azeem Mullappallykayamkulath (Sai Om Journal of Commerce & Management, 2014)
Kerala has emerged as one of the prime tourism destinations in the national and international map and is considered as the tourism hub in the country. The presence of natural resources, skilled manpower, supportive entrepreneurial community, strong government policies, civil society organizations, multitude of micro enterprises, responsible media and responsive tourism industry, provide the state an ideal setting to implement and practice 'Responsible Tourism. Kumarakom, in the State, has the remark of being the first place on the country to have successfully implemented RT. Responsible Tourism (RT) includes three kinds of responsibilities; ‘triple bottom-line’ economic responsibility, social responsibility and environmental responsibility. Though the concept of responsible tourism was there right from 1996, it was after the Cape Town Declaration of 2002 that a detailed picture of responsible tourism - including its aims, and factors evolved. RT encompasses all forms of tourism and seeks to minimize negative economic, environment and social impacts. It generates greater economic benefits to local people and enhances the wellbeing of local communities. It also makes positive contributions to the conservation of natural and cultural heritage, and maintenance of the world’s diversity. This has been made possible by the long term vision and timely intervention by the Department of Tourism, Government of Kerala, which formulated the project in line with the latest international trend in the tourism sector.Considering the success of Responsible Tourism in destinations and the lead position that Kerala enjoys in the global tourism market, this initiative could be replicated in all leading tourism destinations to ensure sustainability of tourism development efforts adopted by Kerala.